Professional Translator’s Ethics and Gender Issue - Diachuk, Lyudmila (Respectus Philologicus, 2018)
This article focuses on the ethical aspects of translation and the question of translators’ responsibility, which nowadays are major issues in Ukraine. The paper demonstrates and reviews numerous cases of copyright infringement. As our research has shown, the texts are sometimes translated into Ukrainian not from their source language, but from Russian translations, which leads to double manipulations with the text. To verify this claim, French women’s belles-lettres texts and their Ukrainian and Russian translations have been analysed and compared. The post-Soviet period of Ukraine’s development has showcased not only the translation-related issues, but also the moral and ethical attitude of translators and publishing houses towards translation as the sphere of copyright. This analysis of Ukrainian translations raises concerns that some book titles, and sometimes the entire belles-lettres works of French women’s prose, have been “copied” from Russian translations. The most significant, in this respect, is the Ukrainian translation of George Sand’s novel “Consuelo”, translated by Viktor Boyko and published in 2011 by the Kharkiv publishing house “Folio”.